A Clinical Study to Assess the Efficacy of Agastimodaka in the Management of Abhyantara Arsha w.s.r. to 1st and 2nd Degree Internal Haemorrhoids. - Sharma, Monika (International Research Journal of Ayurveda & Yoga, 2021)
ARSHA, one of the Ashta-Mahagadas appears at the Guda region, which is a kind of Sadhyapranahar Marma. In Humans, the erect posture results in very high pressure on the valve less rectal venous plexus which makes them prone to this disease. It is a problem related to old age, sedentary lifestyle & dietary factors.Vega Vidharan, ati ushna-tikshana and mamsa ahara leads to Vitiation of Apana vayu, that primarily causes Agni Mandata & Mala avashtamba in the affected individulas. The fourfold treatment protocol given in Ayurvedic context gives more emphasis to start with a Conservative Management -BHESHAJAYA KARMA in Arsha. The present case study includes 45 patients diagnosed with Abhyantra Arsha with chief complaints as Per Rectal Bleeding (Raktasrava), Constipation (Mala bandhta) and Pile Mass (Arsha ankura). An attempt is made to prepare an easily accessible, standard & cost effective palliative mode in terms of AGASTIMODAKA to treat the cases of 1st & 2nd Degree Internal Haemorrhoid. All the ingredients of Agastimodaka are Katu, Tikta, Kashaya Rasatmaka, Madhura Vipaki. It presents as a good Aam Pachaka, shool prashamaka, mala shodhaka and rakta stambhaka. Owing to its Deepana Pachana property, it regulates Agni which improves the digestion and relieves constipation by lowering the pressure on anal varices. A significant relief was observed in all the three study included parameters. Bheshajya Karma has no fear of complications like infection, gangrene and bleeding in comparison to the Allopathic Surgical procedures.